2021
DOI: 10.3390/cancers13153658
|View full text |Cite
|
Sign up to set email alerts
|

The Small-Molecule Inhibitor MRIA9 Reveals Novel Insights into the Cell Cycle Roles of SIK2 in Ovarian Cancer Cells

Abstract: The activity of the Salt inducible kinase 2 (SIK2), a member of the AMP-activated protein kinase (AMPK)-related kinase family, has been linked to several biological processes that maintain cellular and energetic homeostasis. SIK2 is overexpressed in several cancers, including ovarian cancer, where it promotes the proliferation of metastases. Furthermore, as a centrosome kinase, SIK2 has been shown to regulate the G2/M transition, and its depletion sensitizes ovarian cancer to paclitaxel-based chemotherapy. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…We have recently demonstrated that SIK2 is responsible for cell-cycle progression, particularly the G2/M transition, through CEP250 phosphorylation at Ser2392, which is associated with centrosome cohesion [16,30]. In addition, SIK2 mediates mitotic spindle assembly, and its expression is cell-cycle dependent [16]. Further, chemical inhibition of SIK2 by MRIA9 ( 1 ) blocks centrosome disjunction in the late G2 phase [16].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have recently demonstrated that SIK2 is responsible for cell-cycle progression, particularly the G2/M transition, through CEP250 phosphorylation at Ser2392, which is associated with centrosome cohesion [16,30]. In addition, SIK2 mediates mitotic spindle assembly, and its expression is cell-cycle dependent [16]. Further, chemical inhibition of SIK2 by MRIA9 ( 1 ) blocks centrosome disjunction in the late G2 phase [16].…”
Section: Resultsmentioning
confidence: 99%
“…Cell-cycle analysis was performed by incubation of the SKOV3 cells with all three compounds for 24 hours and examined by flow cytometry. We recently described the cell cycle-dependent expression of SIK2, with highest expression levels found in G1 and G2 phases [16]. Control cells were found to be almost evenly distributed between the cell-cycle phases G1, S, and G2, with 34%, 32%, and 24%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations